Visual inspection of cervix with acetic acid in early diagnosis of cin and early cervical cancer - Bindal, Jyoti; Agrawal, Sanju (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The cervix is the commonest site of female genital tract cancer worldwide. Cancer cervix has a long pre-invasive stage, giving an opportunity for its early detection and treatment. Methods: The present study conducted on 400 patients in OPD and Indoor admitted patients during the period of June 2015 to Sept. 2016. Pap’s smears were studied and reported according to the Bethesda classification. On next visit patient attended with cytology report and VIA, VILI was performed and then subjected to colposcopy. Results: The mean age of our population and VIA positivity were 38.2 and 36.8 years. Majority of VIA positive cases had white discharge or pain in lower abdomen as their presenting complaints. The majority of patients who were VIA positive either had cervical ectropion or a hypertrophied cervix. 22 cases were positive on Pap smear and 66 cases were positive on VIA. Only 2 cases positive on Pap smear were missed by VIA. VIA is more sensitive than pap smear. 93.33% of cases, positive on colposcopy were detected by VIA testing. VIA is more sensitive and pap smear more specific in screening of cancer cervix sensitivity ratio of VIA with pap smear is 1.55%. Conclusions: VIA is an attractive test in low resource settings like India. It is simple, inexpensive, low technology test that requires minimal infrastructure for use. It is comparable to cytology in detecting low as well as high grade lesions in terms of sensitivity, specificity and positive predictive value.